Geopolityczny status Królestwa Danii – mit państwa unitarnego - Brańka, Tomasz (Przegląd Politologiczny, 2018)
Pursuant to the Constitution of 1953, the Kingdom of Denmark is a unitary state. How- ever, the status of the Faroe Islands and Greenland actually defies the uniform character of this state. In its broader aspect, this situation undermines the widespread myth of Nordic unity. The official standpoint, explaining the Danish policy of aiding the Faroe Islands and Green- land, points to the long-standing tradition that links Denmark with her overseas territories and the common values that bind them. The Danish responsibility for the development of these territories is also emphasized and financial aid is treated as an expression of the solidarity pol- icy. The paper analyzes the benefits and costs related to maintaining the insular possessions of Denmark.